Verna Lalbeharie joins EdTech Hub as incoming Executive Director - Hub, EdTech (EdTech Hub, 2021)
We are excited to announce that Verna Lalbeharie is joining EdTech Hub as the incoming Executive Director. A native of South Africa, now living in North Carolina (USA), Lalbeharie brings not only 25 years of EdTech expertise to the role, but also a career-spanning commitment to evidence-building in education technology to create a more equitable future for all students. “When…
Keywords: _EdTechHub_Output

Highlights from EdTech and Covid-19: Lessons learned, future plans - Team, EdTech Hub (EdTech Hub, 2021)
On March 2nd EdTech Hub brought together education leaders, including teachers, program managers and policymakers, to reflect on a year of EdTech and Covid-19, discuss the lessons learned so far and consider how we can prepare for the future.  Over 200 people joined from around the world for a lively and thought-provoking discussion. Speakers included:  Helen Grant MP, UK Prime…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Open educational resources - EdTech Hub (EdTech Hub, 2020)
As part of our COVID-19 response, the EdTech Hub is collecting and facilitating access to open educational resources (OER). Open educational resources are teaching, learning and research materials that are made freely available for anyone to access and re-use. These documents are currently stored on Google Drive (no sign-in required). We will add additional distribution […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Call for ideas for EdTech responses to coronavirus (COVID-19) - EdTech Hub (EdTech Hub, 2020)
UPDATE: The call is now closed  We’ve opened a sub-window in partnership with UNHCR for refugee related ideas that respond to COVID-19 school closures. Find full details here. Our call for ideas to respond to the learning emergency caused by COVID-19 school closures is now closed.  We have been delighted and overwhelmed by the huge number […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech Hub: Resources from other organisations - EdTech Hub (EdTech Hub, 2020)
Response efforts and collated resources Global Partnership for Education (GPE)’s response and resources INEE (Inter-Agency Network for Education in Emergencies) collated resources organised by theme COVID-19 ICT4E resources from mEducation Alliance members UNESCO’s response to COVID-19 including information about distance learning tools and national platforms UNHCR’s guidance on distance learning World Bank resources to help […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Designing for Scale: Understanding design principles and learning process for a personalised learning platform in Kenya - EdTech Hub (EdTech Hub, 2022)

Digital Personalised Learning to Improve Numeracy Outcomes in Kenyan Primary School Classrooms - EdTech Hub (EdTech Hub, 2021)

The Impact of a Tech-Supported, School-Based TCPD Model on Learning Outcomes in Tanzania - EdTech Hub (EdTech Hub, 2021)

Optimising Messaging to Promote Returns to School in Ghana for Marginalised Learners - EdTech Hub (EdTech Hub, 2021)

Low-Tech Personalised Learning to Improve Girls' Education in Kenya - EdTech Hub (EdTech Hub, 2021)

Cost-Effective Technology Approaches to Improve Education Outcomes for Girls: Learning from 41 Girls’ Education Challenge projects - EdTech Hub (EdTech Hub, 2022)

EdTech Systems Research - EdTech Hub (EdTech Hub, 2022)

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Conceptual Framework for Monitoring Hybrid Learning Delivery Toward Long-Term System Strengthening and Resilient Education Systems - UNICEF; EdTech Hub (UNICEF, EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Monitoring Hybrid Learning: A Short Guide - UNICEF; EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Operational Guide for Monitoring Hybrid Learning Delivery Toward Long-Term System Strengthening and Resilient Education Systems - UNICEF; EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

O Efeito da COVID-19 na Educação em África e Suas Implicações para a Utilização da Tecnologia Um Inquérito sobre a Experiência e as Opiniões de Educadores e Especialistas em Tecnologia - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

EdTechTools Relaunched with TVET Resources - EdTech Hub; Generation Unlimited (EdTech Hub, 2021)
EdTechHub, Generation Unlimited (GenU), UNESCO and UNESCO-UNEVOC have joined forces to relaunch EdTechTools (formerly the Tools Database): a global repository of education technology tools and platforms designed to help decision makers at all levels in the global education and training community find resources that facilitate and support remote learning. More than a year after the world experienced an education disruption…
Keywords: _EdTechHub_Output

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
Keywords: HLR3; _r:AddedByZotZen

Curated Tools for Teacher Continuous Professional Development - Hub, EdTech (EdTech Hub)
EdTech Hub has created curated lists of teacher professional development (TPD) tools along with evidenced-based advice on how to effectively use them. Because, of course, it’s not only which tool you choose, but how you use it that will determine whether it will lead to better teaching and learning.

Explore EdData Tools - Hub, EdTech (EdTech Hub)
Crowdsourcing Data Technologies for Education in Emergencies

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Education system management / EMIS / education data – EdTechTools - EdTech Hub (2022)

Education system management / EMIS / education data – EdTechTools - EdTech Hub

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub (EdTech Hub)
This systemic mixed-methods study will build evidence on the most feasible approach to GIS-supported teacher allocation in Sierra Leone and assess the impact of this approach on teacher retention and attendance. Discover more...

EdTech for Digital Personalised Learning - EdTech Hub (EdTech Hub, 2022)
Evidence on how technology can be used to maximise the effectiveness of personalised learning and teaching at the level of the student.

EdTech Interventions Database - EdTech Hub (2020)

EdTech companies in Sub-Saharan Africa - EdTech Hub (Airtable, 2020)
Explore the "EdTech companies in Sub-Saharan Africa (see https://tabsoft.co/338AGht for visuals)" view on Airtable.

EdTech Hub Rapid Scans - EdTech Hub

Focus country: Bangladesh - EdTech Hub (2021)

Value for Money Policy and Procedure - EdTech Hub (2020)

Research - EdTech Hub (EdTech Hub, 2021)

Using laptops to distribute video sign language lessons to deaf children in Pakistan - EdTech Hub
We tested different EdTech interventions to find out which ones would be most suitable for providing distance learning for deaf children.

Our Strategy, Part 1: Empowering decision-makers with evidence to improve learning for all - EdTech Hub (EdTech Hub, 2022)
For the last five months, EdTech Hub has been exploring and refining our strategy for advancing evidence in EdTech for low- and middle-income countries. We invite you to explore our thinking for how we will carry out this mission within our context and in partnership with the global EdTech community. Verna Lalbeharie, Executive Director Acknowledgements Thank you to all of…

Our Strategy, Part 2: Deep dive into our approach, focus countries, and theory of change - EdTech Hub (EdTech Hub, 2022)
In Part 2 of our strategy, we go deeper into EdTech Hub’s integrated approach to how we work, where we work, and how that comes together with our topics to inform our theory of change. Verna Lalbeharie, Executive Director The EdTech Hub integrated approach We do research because it is imperative to build deep quantitative and qualitative insight regarding how…

Results – Rapid Scans – The EdTech Hub - EdTech Hub (2023)

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - EdTech Hub (2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…

EdTech Hub Strategy: Mitigating the impact of COVID-19 on equitable education access and learning - The EdTech Hub (2020)

EdTech Hub Quarterly Report October to December 2020 - EdTech Hub Team (2020)

Developing a teacher-focused theory of change for technology-enhanced teaching and learning - EdTech Hub Team (2021)
Internal Brief

Effective Assessment and Progress Monitoring in an Online Environment: A Study in Six Countries - T4 Education; EdTech Hub (EdTech Hub, 2022)
The study was undertaken in six countries – Bangladesh, India, Nigeria, Pakistan, Philippines, and South Africa. The data collection involved focus group discussions with two held in each country..

Designing and monitoring distance teaching and learning interventions: A guide for projects and implementers - Girls' Education Challenge; Fund Manager; EdTech Hub (2021)

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessey, Sarah; Jordan, Katy; Wagner, Daniel; EdTech Hub Team (EdTech Hub, 2021)
Keywords: ⛔ No INSPIRE recid found

Usability Testing of a Mobile-based Learning Management System for Teacher Continuous Professional Development in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Haßler, Björn; Proctor, Jamie; EdTech Hub (The International Journal of Education and Development using Information and Communication Technology, 2023)
The last two decades have seen the growing adoption of mobile devices to enhance the quality of teachers' continuous professional development (TCPD) in low-income countries. Using mobile devices, typically not designed for educational use, presents new usability challenges, preventing teachers from effectively accessing learning materials in learning management systems (LMS). Therefore, it is important to test usability to improve the delivery of TCPD via mobile devices. This study evaluated the usability of TCPD-focused mobile-based LMS accessed via a mobile web browser and mobile app. The evaluation used a hybrid think-aloud method involving 63 teachers from 12 schools in Tanzania. Half of the schools were evaluated using a concurrent think-aloud method, and the other half using a retrospective think-aloud method. The study found that teachers encountered many usability problems in using the mobile app compared to those who accessed the LMS via mobile web browsers. The study also found usability flaws in the registration and login process, poor language translation, technical errors, and issues with quiz questions. These findings show the importance of user testing, even for well-developed LMS, such as Moodle. Additionally, this work provides useful guidance for those who want to implement mobile learning via an LMS in low-income countries.
Keywords: ⛔ No DOI found